Efficacy of Bacillus thuringiensis (Berliner) isolates on fig moth, Ephestia cautella (Walker) Larvae - Baghdad Science Journal (مجلة بغداد للعلوم)
The following dilution 5×10-1, 10-1, 10?2 , 10-3 gm/L for the indigenous isolate of Bacillus thuringiensis bacteria and the commercially isalate were used for experiments against the different stages of fig moth of E.cautella which exposed by filter paper method. The results showed that mortality of larval stages was increased with the increasing concentration of the biocide, in addition to increase in the mortality of the larval stages reached to the highest percentage in the third days of treatment of the larval stage in comparison with the first and second days of exposure. The results also showed that the sensitivity of larval stages was increased in first and second instars while reduced in the last instars .The high percentage of first instar mortality for the indigenous isolate in the concentration of 5×10-1 was 72.8% , while the low percentage of mortality showed in the concentration of 5×10-1 for the fifth instar larvae which was 13.3% in third days of treatment while a high percentage of mortality was showed for the first instar larvae for the commercially isulate in the concentration of 5×10-1 was 59.4% Furthermore, low percentage of mortality was shown in the concentration of 5×10-1 in fifth instar larval which was 8.3% in the third days of treatment. The results also showed that the indigenous isolated was more effective than the commercially produced bacteria for killing larval instars of fig moth E.cautella .The total percentage of larval instar mortality reached to 44.5 % after the third days of treatment in concentration 5×10-1 in the indigenous isolate , and it was 33.8 % in the commercially produced bacteria .